Effectiveness of Audit and Feedback in Improving the Quality of Operative Notes - A Retrospective Observational Study - Maharjan, Leison; Singhal, Aditya; Guragain, Rajendra P S (Journal of Institute of Medicine Nepal, 2019)
Introduction: Surgeons must maintain detailed and accurate operative notes as it is important not only for safe patient care but also for research, audit and medicolegal purposes. But literature has shown that many operative notes are incomplete and illegible. Audit and feedback is a useful strategy to improve such practices which our department has been following. Our aim is to study its effectiveness by comparing the quality of operative notes of 2016 with that of 2014. Methods: Total 96 operative notes, 48 each of the year 2014 and 2016 were studied under 22 parameters including 18 suggested by “Good Surgical Practice” guideline. Each operative notes was analyzed by a single observer for completeness. Parameters of the operative notes of two different years were compared and given the status of either improved, deteriorated or unchanged. Results: Only parameters related to patient identification, date, surgeon’s fullname, postoperative plan were complete in both the years. In comparison to earlier year, in 2016 improvement was seen in parameters such as postoperative diagnosis, details of tissue removed, authors details, closure details, operation time and operative difficulties/ complications and deterioration was seen in hospital number, preoperative diagnosis, procedure, fullname of anesthetist, fullname of scrub nurse, operative findings and signature of the surgeon. Conclusion: Improvement in the quality of the operative notes was not adequate with audit and feedback strategy alone. Hence to increase the effectiveness, other methods such as computerized operative notes and aide-memoire should also be introduced.